Evaluación molecular de diversos receptores y enzimas placentarios en la preeclampsia - Ruiz González, Obdulia (Universidad Michoacana de San Nicolás de Hidalgo, 2009)
Preeclampsia is a hypertensive pathology of pregnancy reported for more than 2000 years. According to the International Society for the Study of the Hypertension in Pregnancy, it is a syndrome characterized by the presence of hypertension and proteinuria, and it is the main cause of maternal-fetal morbidity and mortality in developing countries. Preeclampsia is a multisystemic syndrome characterized by vasoconstriction, metabolic changes, endothelial dysfunction, activation of the coagulation cascade, and increased inflammatory response, to name just a few of the organ systems involved. Currently, it is known that there is a decrease in uterine-placental tissue perfusion generated by the superficial and insufficient invasion of the cytotrophoblast on the uterine spiral arteries, which prevents their remodeling, preserving their original histological structure and their ability to respond to different endothelial modulators; as a consequence, placental hypoxia and ischemia occur. However, the pathophysiological mechanism of preeclampsia is still unknown. The present work consisted of a study with 22 women, in labor, from the Gynecology and Obstetrics Service of the General Hospital “Dr. Miguel Silva ”from Morelia, Michoacán.

La Preclampsia es una patología hipertensiva del embarazo reportado desde hace más de 2000 años. De acuerdo a la International Society for the Study of the Hypertension in Pregnancy, es un síndrome caracterizado por la presencia de hipertensión y proteinuria, y es la principal causa de morbilidad y mortalidad materno-fetal en los países en desarrollo. La Preclampsia es un síndrome multisistémico caracterizado por vasoconstricción, cambios metabólicos, disfunción endotelial, activación de la cascada de la coagulación e incremento en la respuesta inflamatoria, por mencionar solamente algunos de los sistemas orgánicos involucrados. Actualmente, se conoce que existe una disminución en la perfusión tisular útero-placentaria generada por la invasión superficial e insuficiente del citotrofoblasto sobre las arterias espirales uterinas, lo que impide su remodelación, conservando éstas su estructura histológica original y su capacidad de respuesta a los distintos moduladores endoteliales; como consecuencia, se producen hipoxia e isquemia placentarias. No obstante, el mecanismo fisiopatológico de la Preclampsia es aún desconocido. El presente trabajo consistió en un estudio con 22 mujeres, en trabajo de parto, del Servicio de Ginecología y Obstetricia del Hospital General "Dr. Miguel Silva" de Morelia, Michoacán.
Facultad de Ciencias Médicas y Biológicas. Maestría en Ciencias de la Salud
Keywords: info:eu-repo/classification/cti/3; FCMB-M-2009-0032; Sindrome; Enzimas; Preclampsia; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2905